1996
DOI: 10.1029/95jc03861
|View full text |Cite
|
Sign up to set email alerts
|

Coupled dynamics of the South China Sea, the Sulu Sea, and the Pacific Ocean

Abstract: The complex geometry, the seasonally reversing monsoon winds, and the connectivity with the Pacific Ocean all contribute to the coupled dynamics of the circulation in the South China Sea (SCS), the Sulu Sea, and the region around the Philippine Islands. The 1/2 ø, 1.5-layer global reduced gravity thermodynamic Navy layered ocean model (NLOM) is used to separate these components and to investigate the role of each one. When forced by the Hellerman and Rosenstein [1983] (Hit) monthly wind stress climatology, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(212 citation statements)
references
References 23 publications
11
194
2
Order By: Relevance
“…Finally, the U K 37 -based SST averages shifted close to the PF-based winter values as soon as the strait was shut over Stages 4-2. During this time much cooler surface water prevailed in the whole SCS, in part probably advected from the upwelling cell near the northern tip of Luzon (Metzger and Hurlbert, 1996;Pflaumann and Jian, 1999;P. Wang et al, 1995), a mechanism also suggested by the increased nutrient content (see below).…”
Section: Changes In Monsoon-driven Deep-and Surface-water Oceanographymentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the U K 37 -based SST averages shifted close to the PF-based winter values as soon as the strait was shut over Stages 4-2. During this time much cooler surface water prevailed in the whole SCS, in part probably advected from the upwelling cell near the northern tip of Luzon (Metzger and Hurlbert, 1996;Pflaumann and Jian, 1999;P. Wang et al, 1995), a mechanism also suggested by the increased nutrient content (see below).…”
Section: Changes In Monsoon-driven Deep-and Surface-water Oceanographymentioning
confidence: 99%
“…Today the flow advances along the continental margin of South China up to a position south of Hong Kong (Fig. 12A) and is linked to the winter monsoon (Metzger and Hurlbert, 1996). The rich nutrients of the flow originate from an upwelling cell near the north tip of Luzon, whereas the Kuroshio current is nutrient depleted.…”
Section: Variations In the Fertility Of The South China Sea (Premise 6)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the deep passages between the Pacific and Indian Oceans would not have been closed, some of them, particularly the Makassar Straits, would have been significantly narrower suggesting much stronger flows. Shortterm models are very sensitive to small changes in bathymetry (Metzger & Hurlburt 1996) so there is some uncertainty about model results. Glacial falls in sea level would probably have eliminated flow between the Pacific via the South China Sea, the Sunda Shelf and the Indian Ocean (Godfrey 1996) suggesting important changes in currents in the Philippines and Indonesian waters.…”
Section: Pleistocene Impactmentioning
confidence: 99%
“…A large part of the subsurface water entering through the Luzon Strait upwells to the surface layers, gets heated and then flows out of the SCS. The changes in ocean circulation and sea level associated with the monsoons are identified as the primary forcing mechanism of the SCSTF seasonal variability (Metzger and Hurlburt 1996). Meanwhile, its inter-annual as well as decadal variability are considered to be mainly governed by the ENSO Phenomenon (e.g., Qu et al 2004;Wang et al 2006b;Liu et al 2012).…”
mentioning
confidence: 99%